Anion templated assembly of mechanically interlocked structures. - Vickers, MS; Beer, P (2007)
This tutorial review describes the evolution of the field of chemical templation, in particular, emphasising the impact its application has made to the synthesis of mechanically interlocked structures. Recent advances in the use of negatively charged template species for the synthesis of interlocked structures are detailed, with the main focus of this review describing the development of a general anion templation strategy that combines anion recognition with ion-pairing. The versatility of this methodology is demonstrated by the chloride anion templated synthesis of a series of interpenetrated pseudorotaxane, rotaxane and catenane structures. Upon template removal, the mechanically interlocked rotaxanes and catenanes are shown to bind anions within their topologically unique anion binding clefts by virtue of electrostatic and hydrogen bonding interactions, exhibiting a strong selectivity for the chloride halide anion template. The incorporation of the photo-active rhenium(I) bipyridyl signalling group into the rotaxane structural framework highlights the potential of these interlocked systems in future chemical sensor design.